A Model of Health Consumer Protection at Local Administrative Level: the Case of Health Products in Pathumthani Province - Siangprasert, Pikul; Sonsuphap, Rattaphong; Piriyarangsan, Sungsidh (Journal of Health Science of Thailand, 2017)
The aims of this study were to study the relationship among producers, consumers, government sector and local administration and to create a model of health consumer protection at local administrative level using the qualitative method. The study was conducted in Pathumthani Province from May to December 2013; and the methods were comprised of data collection, analysis with the proposal of an innovative consumer protection model. Data were collected through focus group discussion among 51 key informants including 11 health personnel in community hospitals, 30 officers from local administration (city municipality, town municipalities and sub-district municipalities) and 10 public health volunteers. Data were also collected from in-depth interview of 15 key stakeholders including the Provincial Chief Health Officer, the head of the Consumer Protection and Health Pharmacy section, the head of Pharmacy Section of 3 community hospitals, Director of Public Health and Environment Division of 8 municipalities, and 2 presidents of Public Health Volunteers in the province. With regard to the relationship between producers and consumers, it was found that producers lacked of integrity and used advertising media to persuaded consumers. Consumers lacked of products knowledge while government sector, local administration and responsible local administrators were still confronting with the problems in consumer protection and lacked of systematic work procedure which resulted in inefficient performance, lacked of human resource planning and training, unresponsive personnel development in the organizations, lacked of informative evaluation system, and lacked of motivation. Therefore, consumers continue to submit complaints to the government to manage low quality products. With these finding, the authors recommended that consumer protection model for health products should be developed to cover producers, consumers, government sector, local administration and provincial public health. Such model should work in a two-way communication approach, from the central to the local and from the local to the central; and thus highest efficiency of work would be attained. In addition, the authors recommended that multi-sectoral coordination and individual organizational development be ensured. A model of consumer protection of health products was also proposed to include the following factors: “P” is for Participation and Professionalism; “I” is for Innovative Thinking and Innovative Organization; “K” is for KM (Knowledge Management) and KPI (Key Performance Indicator); “U” is for Uniqueness and Unity; and “L” is for Learning Organization.